The caramel Venus and other stories - Terblanche, Tania (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2016)
My collection of stories illustrates the absurdity, the beauty and the pain of being human by depicting experience through fabulation. The intensity of existence comes to light in strange worlds that operate by rules of our inner mechanics, distorted so that only the colours and the shape of our hearts swim underneath. My fiction embodies these realities using the flatness of the fairy tale form while incorporating the humorous, the bizarre and the surreal. Some of the stories build dystopian worlds using the manifestation of the unfamiliar as a mirror of our psyche in an overpopulated and consumer-driven society. Others create contained worlds where the fantastical is fostered only by the narrator being drawn into an inner life. All the stories take us through inner landscapes with the humans, animals and objects around us that can pulse with so much meaning and then none at all.
Keywords: Uncatalogued